Evalating the sustainability of the budget policy in Algeria by estimating the fiscal reaction function during the period 1980-2020 - osmani, sofiane; osmani, mokhtar (Journal of Research in Finance and Accounting, 2022)
This study examines the sustainability of budgeting policy in Algeria by exploring government’s reaction to rising public debt accumulation via the estimation of a fiscal reaction function using The Autoregressive Distributed Lag Model (ARDL. Our findings suggest that government’s fiscal behavior is consistent with the intertemporal budget constraint, but the fiscal adjustment in primary balance debt appears to be very low Compared to the increase in public